Nonequilibrium statistical mechanics - Zwanzig, Robert (Oxford University Press, 2001)
This book presents the main principles and methods of nonequilibrium statistical mechanics, a topic studied by both chemists and physicists. It is written for graduate students and scientists who already have knowledge of basic equilibrium statistical mechanics and who are interested in the more complex field of time-dependent nonequilibrium statistical mechanics.